Penerapaan Teknik Regulasi Diri Untuk Meningkatkan Kemandirian Belajar Siswa di SMA Negeri 9 Gowa - Najdaeni Najdaeni; Sulaiman Samad; Rosmini Rosmini (Indonesian Journal of School Counseling: Theory, Application, and Development, 2021)
This experimental research was conducted at SMA Negeri 9 Gowa with the research subjects being students of class XI MIPA 5 with a total of 10 people. The problem in this study is that students in class XI MIPA 5 experience low learning independence. The approach in this study is quantitative with experimental research methods. Collecting data using interviews, direct observation and questionnaire instruments. Data analysis used quantitative analysis. The results of this study indicate that (1) students' learning independence after being given treatment in the form of self-regulation exercises increases. (2) The application of the self-regulation technique has a positive effect on increasing student learning independence at SMA Negeri 9 Gowa. The approach in this research is quantitative research with the type of research is Pre-Experimental Designs. The results of the validation test were then tested on students with the test results showing students were able to take part in a series of Self Regulation Technique activities in order to increase learning independence. Thus the results of this study (1) students' learning independence before being given self-regulation techniques were in the low and medium categories. (2) students' learning independence after being given treatment in the form of self-regulation exercises increased. (3) The application of the self-regulation technique has a positive effect on increasing student learning independence at SMA Negeri 9 Gowa.